Pengembangan Bahan Ajar Analisis Struktural Novel Awan Karya Syafrudin Pernyata pada Mata Pelajaran Bahasa Indonesia Tingkat SMA - Lumban, Yunita; Arifin, Syaiful; Mulawarman, Widyatmike Gede; Suhatmady, Bibit; Hudiyono, Yusak (Syntax Corporation, 2025)
The purpose of this research is to describe, among other things: 1) the structural analysis of Robert Stanton applied to the novel Awan by Syafruddin Pernyata, 2) the instructional materials containing the structural analysis of the novel Awan by Syafruddin Pernyata, and 3) the effectiveness of the instructional materials developed from the structural analysis of the novel Awan by Syafruddin Pernyata. This study employs a reflective, recursive, design, and development (R2D2) model research method. This method is used to produce and test a product using instructional materials based on the structural analysis of the novel Awan by Syafruddin Pernyata. The results of the study show that the instructional materials based on the structural analysis of the novel Awan by Syafruddin Pernyata were validated by a content expert who gave a score of 79.25%, which falls into the